1997
DOI: 10.1152/ajplung.1997.273.3.l676
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the interleukin-10 gene by alveolar macrophages in interstitial lung disease

Abstract: Idiopathic pulmonary fibrosis (IPF) and bronchiolitis obliterans with organizing pneumonia (BOOP) are interstitial lung diseases of unknown pathogenesis. Alveolar macrophages play a major role in the regulation of the inflammatory response in these diseases through their ability to produce cytokines that modify the inflammatory response. Tumor necrosis factor-alpha (TNF-alpha) and interleukin-10 (IL-10) exhibit proinflammatory and anti-inflammatory actions, respectively, and thus an imbalance in the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 0 publications
3
40
0
3
Order By: Relevance
“…Taken together, these findings suggest that fibroblast and myofibroblast accumulation in the lungs of IPF patients could occur as a result of impaired sensitization to Fas-induced apoptosis. They are also consistent with the developing notion that fibrosis can progress in the absence of a robust inflammatory response associated with reduced levels of proinflammatory sensitizing molecules such as TNF-a, IFN-g, and PGE 2 (1,(24)(25)(26).…”
supporting
confidence: 86%
“…Taken together, these findings suggest that fibroblast and myofibroblast accumulation in the lungs of IPF patients could occur as a result of impaired sensitization to Fas-induced apoptosis. They are also consistent with the developing notion that fibrosis can progress in the absence of a robust inflammatory response associated with reduced levels of proinflammatory sensitizing molecules such as TNF-a, IFN-g, and PGE 2 (1,(24)(25)(26).…”
supporting
confidence: 86%
“…In the normal human lung, AMs constitutively produce low levels of IL-10 in their role as mediators of the host defence response, and this protein is upregulated by both LPS stimulation and TNF-a. The relation between IL-10 and TNF-a has been extensively investigated in numerous inflammatory disorders including IPF, where several studies have shown increased TNF-a in IPF despite evidence suggesting that IL-10 is also increased in these patients 6,7 (Freeburn R, Millar A, unpublished data). In a previous study we showed using semiquantitative PCR that expression of IL-10 mRNA was significantly increased in AMs from patients with IPF compared to controls.…”
Section: Resultsmentioning
confidence: 99%
“…4 In the normal lung, IL-10 is constitutively produced at a low level representing an endogenous feedback factor for the control of the inflammatory response. 5 The aetiology of IPF is unknown, but AMs from these patients exhibit elevated levels of TNF-a relative to IL-10, suggesting that in this disease the normal homeostatic mechanisms fail to regulate the TNF-a inflammatory response 6,7 (Freeburn R, Millar A, unpublished results). Differences in lipopolysaccharide (LPS)-induced IL-10 secretion have been related to corresponding differences in mRNA production implicating transcription as the principal mechanism in variable IL-10 production.…”
Section: Introductionmentioning
confidence: 99%
“…These important immunological activities are implicated in several human diseases such as psoriasis [15][16][17], rheumatoid arthritis [18][19][20], and inflammatory lung and bowel diseases [21,22]. In this context, the study of IL-10 members, their interaction with receptors, and elicited cell signaling cascade, are important to understand the basis of both immunoregulation and associated diseases, establishing strategies to modulate or to control these health conditions and illnesses.…”
Section: Introductionmentioning
confidence: 99%